THE IMPORTANCE OF PRESERVATION OF AMBIENT CONNECTED TO THE TOURISM PHENOMENON GENERATED BY THE EXPLORATION OF HOT WATERS: THE CASE OF THE CIA THERMAS OF THE RIO QUENTE - Caroline Tristão de Alencar Magalhães (Sociedade & Natureza)
The tourist complex Pousada do Rio Quente located at Mountain range of Caldas atRio Quente city at 17º 46’30’’ south latitude e 48º 44’52’’ west Greenwich, is composed ofhydrothermal park called Hot Park and a net of hotels with hot water swimming pools knownas: Tourist Hotel (1), Pousada Hotel (2), Pousada do Rio Quente Chalés (4), Recanto dasÁguas quentes (6), Rio Quente Suite & Flats(5)and Hot Park (3).The thermal water sources that appear in the neighborhoods of the region of RioQuente had been discovered in 1722 by Bartolomeu Bueno da Silva who initially explored theregion searching for gold precious rocks. In 1916 Dr. Ciro Palmerston Guimarães resident inthen the city of Caldas Novas acquires 49 alqueires of land where was the riverbed or RioQuente in Caldas Velha located at 27 kilometers of Caldas Novas. In 1994 the Pousada doRio Quente Resorts acquires eighteen habitations units and a room of the CondominiumPousada do Rio Quente, organized under the form of Apart-Hotel. In 1996 due to demand oftourists the airport of Caldas Novas is created. In 1997 an aquatic park with 8.500m2 wasinaugurated being 4000 m2 composed of swimming pools with natural hot water and the LazyRiver. In 1999 the Largo da Ponte is inaugurated which offers new attractions for the touristsas old-time photos, cafeteria, ecological diving, kiosk for credits selling, consisting yet adivision for the Parque das Fontes, whose access is allowed only for them houses of thetourist complex, and the Hot Park that is opened the public in general. In January of 2000 theprocedures for implantation of the System of Ambient Management based on NBR ISO14001 are determined, in this same time the dependences of the Hot Park are extended and inJuly of the same year the First Week of the Environment in the Pousada do Rio quente withthe participation of about 3000 people was promoted. In July is inaugurated the Rio QuenteSuíte and Flat, organized in the format of Apart-Hotel. In May of 2001 Second Week of theEnvironment was made and counted with the participation of more than 4000 people. In Julyof 2001 there was accomplished the initial auditorship for BVQI in agreement with NBR ISO14001 and also another block of the Suite & Flat Hotels were inaugurated.